2002
DOI: 10.1108/09576060210436669
|View full text |Cite
|
Sign up to set email alerts
|

Implementing strategies successfully

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 7 publications
1
63
0
2
Order By: Relevance
“…Strategy implementation is the most difficult and important part of strategic management. No matter how superior its formulated strategy, a hotel will not benefit if it is implemented incorrectly (Aaltonen and Ikavalko, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Strategy implementation is the most difficult and important part of strategic management. No matter how superior its formulated strategy, a hotel will not benefit if it is implemented incorrectly (Aaltonen and Ikavalko, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A feature of the literature reviewed (Aaltonen & Ikavalko, ; Galbraith & Kazanjian, ; Ho et al, ; Hrebiniak & Joyce, ; Stonich, ; Thompson et al, ; Thorpe & Morgan, ; Waterman, Peters, & Phillips, ) is the consistent view that strategy implementation as a concept is made up of similar and identifiable factors. These common factors are organizational structure, organizational culture, leadership, operational planning, resource allocation, communication, people, and control (see also the McKinsey's 7S Model by Waterman et al, ; and the expanded 8 S's Model by Higgins, ).…”
Section: Definition Of Strategy Implementation and Its Representativementioning
confidence: 99%
“…Without an executable plan -and the resources needed to implement that plan -even the most innovative strategy is merely words on paper." (p. 153) It has been noted that organisations have difficulties in implementing their strategies (Aaltonen and Ikavalko, 2002). Research has suggested that half of the decisions made by an organisation fail (Nutt, 1999), whereas nearly 70 percent of strategies and strategic plans and decisions are not implemented successfully according to Okumus, 2003;and Corboy and O'Corrbui, 1999.…”
Section: Introductionmentioning
confidence: 99%